Environmental Policy as a Tool for Sustainable Development (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue aims to collate original research papers, reviews, and perspectives that address the application of environmental policies as tools for sustainable development. We selected papers that utilize both traditional and innovative approaches, including surveys, databases, machine learning, and modeling applications. Additionally, this Special Issue presents submissions addressing the decision-making processes involved in the design of policy measures, the frameworks under policy design, the evaluation of current environmental policies, and the underlying connections between policy measures, climate change mitigation, and sustainability.